ANALISIS PERSEPSI PETANI DALAM PENGGUNAAN BENIH PADI UNGGUL DI KECAMATAN MUARA PAWAN KABUPATEN KETAPANG - Radian, Elly Hendrawati, Erlinda Yurisnthae, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2014)
Rice is an important commodity for more than 90 percent of Indonesian peoples as a staple food source. As an effort to increase the production of rice is the technology adoption for improved rice seeds. Muara Pawan District is one of the production center of rice in Ketapang Regency, with total area of 3,909 hectares of rice fields. But with its potential, the use of local varieties of paddy seeds was still high, when compared with the use of superior rice seed varieties, where the percentage of farmers users local varieties of rice seeds 64.83 % , while the percentage of farmers users superior rice seeds 35,17 %. Based on the the problem, this research aimed to investigate the perceptions of farmers on the use of prime rice seeds and its correlation with the characteristics of farmers. The result of the analysis showed that the perception of farmers on the use of prime rice seeds in Muara Pawan District Ketapang Regency in general classified as poor level (44.0 % of respondents). Besides, the peception that classified for good level only 39.4 % of respondents, and the perception that classified as bad level only 16.6 %. In addition, the results showed that the perceptions of the use of prime rice seeds to farmers characteristics have a correlation with the correlation value 0.531 and significant value 0.008 (<0.05). The variable that is significantly correlated with the farmer’s percepton is the interaction among farmers, means that farmers who had higher intensity of interactions will be more aware of the advantages of prime rice seeds than the farmers who had lower interaction intensity. Key words: farmers' perception, improved rice seeds